2007
DOI: 10.1016/j.jtcvs.2007.04.017
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide levels predict outcome after neonatal cardiac surgery

Abstract: In neonates undergoing cardiac surgery, an increase in B-type natriuretic peptide 24 hours after surgery predicts poor postoperative outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 24 publications
(48 reference statements)
0
37
2
2
Order By: Relevance
“…Few studies have reported on the prognostic value of BNP in patients with univentricular heart, most of which had a relatively short follow-up period [26][27][28]. Hsu et al showed that high BNP concentration 12 h after BDCPA procedure predicts a longer hospital stay and a higher risk of unplanned intervention after BDCPA [29].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported on the prognostic value of BNP in patients with univentricular heart, most of which had a relatively short follow-up period [26][27][28]. Hsu et al showed that high BNP concentration 12 h after BDCPA procedure predicts a longer hospital stay and a higher risk of unplanned intervention after BDCPA [29].…”
Section: Discussionmentioning
confidence: 99%
“…(2007) опре-делили, что у новорожденных повышение BNP в раннем послеоперационном периоде (первые 24 ч после опера-ции) ассоциировалось с увеличением времени искусствен-ной вентиляции легких и вероятности синдрома малого сердечного выброса, внезапной смерти в течение 6 мес. после оперативного вмешательства и трансплантации сер-дца [67]. Группа других исследователей под руководством Shih С.Y.…”
Section: прогностическая роль натрийуретических пептидовunclassified
“…Higher BNP values are associated with severity of illness [87], the duration of mechanical ventilation [88], intensive care unit stay [88], the need for inotropic support [89] and low cardiac output syndrome [88]. Cantinotti et al reported, in 162 children who underwent cardiac surgery, that peak BNP was an independent predictor of time to extubation in older children [90].…”
Section: Reviewmentioning
confidence: 99%